Operational experiences tuning the ATF2 final focus optics towards obtaining A 37 nano-meter electron beam IP spot size - White, G; Seryi, A; Woodley, M; Marin, E; Kamiya, Y; Bai, S; Bolzon, B; Kubo, K; Kuroda, S; Okugi, T; Tauchi, T; Bambade, P; et al. (2010)
The primary aim of the ATF2 research accelerator is to test a scaled version of the final focus optics planned for use in next-generation linear lepton colliders. ATF2 consists of a 1.3 GeV linac, damping ring providing low-emittance electron beams (<12pm in the vertical plane), extraction line and final focus optics. The design details of the final focus optics and implementation at ATF2 are presented elsewhere [1]. The ATF2 accelerator is currently being commissioned, with a staged approach to achieving the design IP spot size. It is expected that as we implement more demanding optics and reduce the vertical beta function at the IP, the tuning becomes more difficult and takes longer. We present here a description of the implementation of the tuning procedures and describe operational experiences and performances.